Antecedents of status consumption among women and the roles of hedonism and cultural value orientation - Teo, Boon Chui (2011)
People crave for status and status recognition. This status struggle plagues today’s consumer societies. The fetish with status-seeking which manifests into consumption of status goods has emerged among women who have experienced increased economic and social influence. While previous studies have presented different factors influencing status consumption, few studies have delved into individual traits such as consumer vanity and attitudes toward money as antecedents on status desires. Marketing research has largely ignored female consumers’ capacity for hedonic orientation associated with status purchase motivations. The current study investigates the phenomenon of status consumption behavior among Malaysian women. Specifically, vanity, money attitude and non-functional product benefits are investigated as antecedents of status consumption. The mediating effects of individual hedonic orientation and moderating role of cultural values of individualism-collectivism are also examined. Methodology utilized mixed methods research approach. Women form the unit of analysis. Three phases of field studies were conducted. Phase 1, a preliminary study using survey approach on 80 respondents identified status-signaling products. In Phase 2, focus group discussions probed hedonic and symbolic product benefits and characteristic of individual hedonic orientation among women. Using quota sampling, Phase 3 involved a survey on a sample of 500 female respondents. Using Structural Equation Modeling, path relationships between three latent antecedent factors and dependent variable, one mediator variable and two moderators were evaluated. Findings suggest the prevalence of status consumption among Malaysian women. Findings indicate women exhibited power, quality and achievement attitude towards money and were associated with status consumption. Attitude towards non-functional product benefits in the form of imaginal, voyeuristic and symbolic benefits stimulated status consumption. Contrary to popular beliefs, vanity did not relate to status consumption among Malaysian women. Individual hedonic orientation mediated the relationships between attitude towards money and nonfunctional product benefits with status consumption. Consumer vanity had no direct effects with status consumption via individual hedonic orientation. Moderating results revealed collectivists were stronger than individualists in influencing interrelationships. Findings offered theoretical implication that status model is still relevant today. Managerial implications followed by limitations and future research directions were addressed.